Types of Speech Acts Spoken by Livi Redden on Video “What Nobody Tells You About Your Twenties” (2023) on Youtube - x, Reviana; Rofik, Abdur (Metaphor, 2025)
This study is aimed to find out (1) types of speech acts and (2) the function of types of speech acts spoken by Livi Redden on video "What Nobody Tells You About Your Twenties” (2018) on YouTube. The method used in this research is qualitative approach. The research reveals the intricate ways in which speech acts contribute to the effectiveness of Redden's communication and engagement with her audience. The object of this study is Livi Redden and the subject of this study is Livi Redden’s utterance. In collecting data, the techniques applied by the researcher are watching video, downloading transcript, picking, categorizing, and phrasing the data. To analyze the data, the researcher uses John R. Searle’s theory of speech act. It is done through some steps as displaying, explaining, and intrepreting. The findings provide insights into the performative aspects of online discourse, highlighting the role of speech acts in shaping viewers' understanding and responses.The result of this research shows that: first, the types of speech acts in the video which spoken by Livi Redden exists in this study. Those are; assertive, expressive, commissive, directive, declarative. Second, the functions of the types of speech acts according to Livi Redden’s utterance, those are; commanding, refusal, espressing feelings, blaming, predicting, claiming.